Persepsi Peserta Pelatihan Terhadap Pemanfaatan Google Sites Dalam Pembelajaran - Joko Waluyo (Andragogi: Jurnal Diklat Teknis Pendidikan dan Keagamaan, 2021)
[TRAINING PARTICIPANTS' PERCEPTIONS OF USING GOOGLE SITES IN LEARNING] The rapid development of internet technology in the digital era facilitates all activities of human life without exception in the field of training which has easy access in optimizing learning. One of the internet technologies that can be implemented in the application of learning during the COVID-19 period is by utilizing Google sites. The purpose of this study was to determine the trainees' perceptions of the use of google sites in learning. This study uses a survey method approach with a descriptive nature which aims to describe the circumstances or phenomena that occur. The results of the study indicate that multimedia-based learning media training with google sites is very necessary for participants in online learning and is useful for participants to provide subject matter to students because the content on google sites can be adapted to the needs of the learning process.